2019
DOI: 10.1590/1678-4499.2010197
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cover crops on soil hydraulic properties and yield in a persimmon orchard

Abstract: This study evaluated the effects of cover crops on yield and soil hydraulic properties of a persimmon orchard in Turkey. Soil samples were taken from 0-20 and 20-40 cm. Profiles of a clay soil and field capacity, permanent wilting point, available water capacity and saturated hydraulic conductivity of the samples were determined. Festuca rubra subsp. rubra, Trifolium repens, Festuca arundinacea, a mixture of them [Trifolium repens (40%) + Festuca rubra rubra (30%) + Festuca arundinacea (30%)], Vicia villosa R.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 30 publications
3
16
0
Order By: Relevance
“…Similar results were observed in a study, where cover crops improved soil moisture (Obalum et al, 2011). Demir et al (2019) found that highest rises were in the Vicia villosa Roth treatment, diminishing the BD by 12.7% while rising the AWC by 19.4%, SOM by 63.5%, and SSI by 9.4% in the 0-20 cm soil depth in the apricot orchard with clay soil. Steele et al (2012) reported that CCs improved physical properties of soils.…”
Section: Field Capacity (Fc) Permanent Wilting Point (Pwp) and Availsupporting
confidence: 86%
See 3 more Smart Citations
“…Similar results were observed in a study, where cover crops improved soil moisture (Obalum et al, 2011). Demir et al (2019) found that highest rises were in the Vicia villosa Roth treatment, diminishing the BD by 12.7% while rising the AWC by 19.4%, SOM by 63.5%, and SSI by 9.4% in the 0-20 cm soil depth in the apricot orchard with clay soil. Steele et al (2012) reported that CCs improved physical properties of soils.…”
Section: Field Capacity (Fc) Permanent Wilting Point (Pwp) and Availsupporting
confidence: 86%
“…Troeh et al (2003) reported that the influence of CCs on changes in BD and total F usually results from the roots of the crops. CCs have been found to decrease soil BD and increase soil macroporosity (Villamil et al, 2006;Candemir and Gülser, 2010;Blanco-Canqui et al, 2011;Demir and Işık, 2019a). These researchers explained that CCs protect the soil from compaction, as well as it increases soil organic carbon concentrations which lowered the soil BD in the subsurface depth.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…For example, increased SOM content and aggregate stability and decreased soil bulk density were observed after four years of cover cropping with white clover in wine grapes [56] and after seven years of surface applications of alfalfa hay or bark mulch [44] in irrigated apples. Similar findings were reported after six years of mulch and compost applications in a heavily eroded apple orchard [57] and after only two years of leguminous cover-cropping in an apricot orchard [58]. Amendment-driven changes in soil physical properties can increase soil water content (θ) and change the soil moisture potential (ψ) and characteristic curve (θ vs. ψ) of orchard soils.…”
Section: Effects Of Organic Soil Amendments On Soil Nutrient Dynamicssupporting
confidence: 71%